Hematopoietic G‐protein‐coupled receptor kinase 2 deficiency decreases atherosclerotic lesion formation in LDL receptor‐knockout mice. Issue 1 (9th October 2012) - Otten, Jeroen J. T.; de Jager, Saskia C. A.; Kavelaars, Annemieke; Seijkens, Tom; Bot, Ilze; Wijnands, Erwin; Beckers, Linda; Westra, Marijke M.; Bot, Martine; Busch, Matthias; Bermudez, Beatriz; van Berkel, Theo J. C.; et al.
Abstract : Leukocyte chemotaxis is deemed instrumental in initiation and progression of atherosclerosis. It is mediated by G‐protein‐coupled receptors ( e.g., CCR2 and CCR5), the activity of which is controlled by G‐protein‐coupled receptor kinases (GRKs). In this study, we analyzed the effect of hematopoietic deficiency of a potent regulator kinase of chemotaxis (GRK2) on atherogenesis. LDL receptor‐deficient ( LDLr –/– ) mice with heterozygous hematopoietic GRK2 deficiency, generated by bone marrow transplantation ( n =15), displayed a dramatic attenuation of plaque development, with 79% reduction in necrotic core and increased macrophage content. Circulating monocytes decreased and granulocytes increased in GRK2 +/– chimeras, which could be attributed to diminished granulocyte colony‐forming units in bone marrow. Collectively, these data pointed to myeloid cells as major mediators of the impaired atherogenic response in GRK2 +/– chimeras. LDLr –/– mice with macrophage/granulocyte‐specific GRK2 deficiency ( LysM‐Cre GRK2fl ox/flox ; n =8) failed to mimic the aforementioned phenotype, acquitting these cells as major responsible subsets for GRK2 deficiency‐associated atheroprotection. To conclude, even partial hematopoietic GRK2 deficiency prevents atherosclerotic lesion progression beyond the fatty streak stage, identifying hematopoietic GRK2 as a potential target for intervention in atherosclerosis.—Otten, J. J. T., de Jager, S. C. A., Kavelaars, A., Seijkens, T., Bot, I., Wijnands, E., Beckers, L., Westra, M. M., Bot, M., Busch, M., Bermudez, B., van Berkel, T. J. C., Heijnen, C. J., Biessen, E. A. L. Hematopoietic G‐protein‐coupled receptor kinase 2 deficiency decreases atherosclerotic lesion formation in LDL receptor‐knockout mice. FASEB J. 27, 265–276 (2013). www.fasebj.org